“I want to see more of this, where our stories are told”: Exploring iwi cultural landscapes through photovoice - Kimiora Raerino; Rau Hoskins; Kara Beckford; Aneta Cram (Wellbeing, Space and Society)
Indigenous photovoice was utilised to explore the iwi cultural landscapes of Ngā Hau Māngere, Aotearoa New Zealand, through the unique perspectives of ten Mana Whenua photographers. This study demonstrates how iwi cultural landscapes, such as signage, buildings, artworks, and ‘nature’ features, function as vital expressions and facilitators of iwi identity, history, and values. By employing Te Aranga Design Principles as an analytic tool, the research provides insights into the significance of iwi cultural landscapes, their meanings, and their role in evoking emotional and cultural connections. The findings highlight the importance of these landscapes in reinforcing Indigenous identity and sovereignty, strengthening community resilience, and promoting wellbeing. Advocating for Mana Whenua co-design and collaboration, this study underscores the urgent need for genuine engagement to create more inclusive and culturally responsive urban spaces while contributing to global discussions on integrating and grounding Indigenous knowledge into urban design and planning.